PENINGKATAN KESADARAN KESEHATAN DAN KESELAMATAN KERJA (K3) UNTUK PEKERJA USIA 30 TAHUN KEATAS DENGAN TELEVISON COMMERCIAL DAN POSTER - Ria Sapitri; Andrean Sebastyan Helmi; Muhammad Adi Sukma Nalendra (LPPM-ITEBA, 2022)
Work accidents often occur in every company, where the situation can occur due to environmental factors or worker negligence, most cases occur due to worker negligence, where they do not realize how dangerous it is if they do not follow work safety regulations (K3). Employees who often neglect work safety are young workers who have just graduated from high school (SMA), where they have no experience in the field, so they are not yet aware of the importance of work safety. Therefore, a solution that is not too heavy is needed, but very effective, namely infographics. The purpose of this design is to make workers more aware of work safety, considering that young people often use cellphones to view social media, of course infographics are the right way so that information can be conveyed properly. The research methodology for collecting data is using descriptive qualitative research methods in the form of literature studies to fulfill the main foundation data such as the case that occurred at PT X, conducting interviews with young workers who are potential resource persons, distributing questionnaires to young workers related to the topic.